Impact of neutrons on the RadFET dose response when exposed to mixed-fields. (February 2021) - Marzo, M.; Alia, R.G.; Infantino, A.; Brucoli, M.; Danzeca, S.
Abstract: The Radiation MONitoring (RadMON) system is widely employed at CERN to measure the radiation levels in the accelerators, as well as the degradation of electronics located in the Large Hadron Collider (LHC) tunnel and shielded areas. Radiation Field Effect Transistors (RadFETs) integrated in the RadMON specifically measure the Total Ionizing Dose (TID) in the accelerators complex and are affected in turn by the CERN radiation field. The CERN High energy AcceleRator Mixed-field test facility (CHARM) has been built with the intention of reproducing different mixed-fields (atmospheric, space, accelerators, ground, …), to test electronics when exposed to specific radiation environments. Among these fields, LHC-like environments are reproduced to test the RadMON's electronic components: the main goal is a full characterization of the RadMON response and the monitoring of its degradation, when it is exposed to the LHC radiation field. FLUKA Monte Carlo simulations are crucial at this stage as a powerful tool to reproduce and calibrate the RadMON response. Our present FLUKA Monte Carlo model of the RadFET is well representative of its experimental dose response to the CHARM mixed-field, in unshielded layout. However, the simulations-experiments agreement in lateral shielded positions is less accurate, probably due to the neutron component of the field. This paper focuses on the study of the RadFET dose response to neutrons, when the dosimeter is irradiated by mixed-fields. FLUKA Monte Carlo simulations and neutron test campaigns performed at ILL (Institut Laue Langevin) and LPSC (Laboratoire de Physique subatomique et de Cosmologie) in Grenoble, as well as at CERN are compared, to further investigate and fully characterize the RadFET response to neutrons. The simulations-measurements agreement is within the experimental uncertainties, while an overall agreement within a factor 2 is found in positions shielded by the movable walls, at CHARM. The test campaign showed the RadFET is insensitive to the thermal neutron component of the mixed-field at CHARM. Abstract : Highlights: A two-steps Monte Carlo approach is proposed to simulate the RadFET dose response. Experimental campaigns were conducted to test the RadFET sensitivity to neutrons. Measurements were performed using 14 MeV and thermal neutrons beams. Thermal neutrons at CHARM give a negligible contribution to the total dose. The overall experiments-simulations agreement is within a factor 2.